Discrimination as a Global Paradigm: United Kingdom and United States of America in Focus - Ousu Mendy (Faculty of Law Universitas Lampung, 2023)
In spite of the commitment of the international community to the protection of human rights, equality before the law still remains a global problem. This research focuses on the problem of discrimination as a worldwide issue imposed on society. The aim of this research is to present a global perspective on the current threat of discrimination as a paradigm shift from equality before the law as a universal principle articulated in Universal Declaration of Human Rights which is the principal human rights instrument. A normative research method is used in this work with extensive theoretical approach. In this method, secondary data like journal articles, books and international conventions are used to support the basis of this research. This research finds that, for some time now, democracy experiences setback by different factors such governance in the forms of autocracy, and unconstitutional change of governments through of coup d' état. The impact of discrimination on equality before the law as a rule of law in modern governance is as topical as it is ever destructive. Women also have made significant progress in many areas over time in places where discrimination is low, including closing some gender gaps. The load of adversity is shared between men and women in our troubled world in a very unequal manner, nevertheless.